2023
DOI: 10.3390/agronomy13051227
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in Various Physio-Biochemical Parameters and Yield Traits of Faba Bean Due to Humic Acid Plus 6-Benzylaminopurine Application under Deficit Irrigation

Abstract: Implementing the deficit irrigation pattern has become a major strategy in crop production systems. However, using less water than is required to irrigate crops is associated with changes in plant physiology and lower productivity. Therefore, the current research aimed to assess the integrated effect of humic acid and cytokinin on faba bean under water deficit. Under two irrigation levels (full irrigation, FI and deficit irrigation, DI), two humic acid treatments (without addition, H0 and with addition of 10 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…The enhancement of AsA, TPC, and total antioxidant content in sprayed plants with biostimulantsbased amino acids might be correlated to the improvement of the photosynthesis system in plants which leads to the accumulation of secondary metabolites. Furthermore, several authors confirmed that foliar application with amino acid bio-stimulant plays an important role in antioxidant metabolism in plants (Hildebrandt et al, 2015;Weiland et al, 2015;El-Beltagi et al, 2023;Ramadan et al, 2023).…”
Section: Ascorbic Acid Total Phenol Content and Total Antioxidantsmentioning
confidence: 91%
“…The enhancement of AsA, TPC, and total antioxidant content in sprayed plants with biostimulantsbased amino acids might be correlated to the improvement of the photosynthesis system in plants which leads to the accumulation of secondary metabolites. Furthermore, several authors confirmed that foliar application with amino acid bio-stimulant plays an important role in antioxidant metabolism in plants (Hildebrandt et al, 2015;Weiland et al, 2015;El-Beltagi et al, 2023;Ramadan et al, 2023).…”
Section: Ascorbic Acid Total Phenol Content and Total Antioxidantsmentioning
confidence: 91%
“…The fungus chaff is loose and porous which can increase soil porosity and benefit the growth and development of alfalfa root. Humic acid can increase soil nutrient content and improve soil physical and chemical properties [53][54][55], promoting the root growth of alfalfa. In this experiment, when the amount of modifier is 10 g/kg, most root indexes are improved significantly.…”
Section: Effects Of Modifier and Water-soluble Fertilizer On Alfalfamentioning
confidence: 99%
“…As shown in Figure 2e, the proline content of DM was significantly higher than that of DS. Proline can promote cell membrane osmoregulation and maintain membrane stability to alleviate drought stress, as an osmoregulatory protective substance accumulated in plants under adverse stress conditions [36,37]. Therefore, the increased drought tolerance under DM could improve the pollen viability, pollen germination rate, and filled grain percentage relative to DS.…”
Section: Effects Of Exogenous Meja Application On Grain Yieldmentioning
confidence: 99%